Eugenia no Brasil: análise do discurso "científico" no Boletim de Eugenia: 1929-1933 - Rocha, Simone (2010)
This research is related to eugenics in Brazil. It aims to discuss the scientific speech of the authors who contributed to the journal Boletim de Eugenia published monthly from 1929 until 1933. It takes into account its repercussion in our country as well as its relation to the social transformations that were taking place at that moment here. This thesis contains an introduction and five chapters. Chapter 1 deals with the origins of word eugenics and its developments. Chapter 2 discusses about some subjects related to eugenics in Brazil, from the colonization to the Republic. Chapter 3 comments on some eugenics views which are present in Boletim. Chapter 4 analyses the scientific speech related to eugenics. Chapter 5 provides some final remarks on the subject. This study led to the conclusion that the defence of eugenics as a science is present in the speech of the most part of the authors who published in Boletins de Eugenia and is related to the constitution of the Brazilian folk. In some cases such as Octavio Domingues and Roquette-Pinto, for instance, the arguments were founded in scientific evidences. However, in the speech of most authors we can find the view highly spread among high class: the search of the whitening of the race and the superiority of the white race. Such idea, mainly guided by prejudice and devoid of scientific foundation may be found in the speech of Renato Kehl, for instance